Neurosurgical departments functioning during the COVID-19 pandemic - report - Zygmunt Siedlecki; Karol Nowak; Maciej Śniegocki (Kazimierz Wielki University, 2021)
We present a short article on the actual state of functioning of neurosurgical departments, performing neurosurgical procedures during the COVID-19 pandemic on the example of our department - Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery of Ludwik Rydygier Collegium Medicum of Nicolaus Copernicus University. The pandemic disrupted so far, proper work of neurosurgical departments and put neurosurgeons in a new reality. Despite the widespread exacerbation of spine diseases, they were pushed to the background. Many neurosurgical departments have been converted into COVID-19 isolation departments. We present a brief report on the actual state of the work of neurosurgeons and that a year after the pandemic began, the work of neurosurgical departments is still disrupted and the prospect of performing non-urgent neurosurgical procedures is uncertain.